The House of Wisdom - Heide, Florence Parry; Gilliland, Judith Heide; e (New York : DK, 1999)
Ishaq, the son of the chief translator to the Caliph of ancient Baghdad, travels the world in search of precious books and manuscripts and brings them back to the great library known as the House of Wisdom.
School Library Journal.
Book Links (A.L.A.).
Booklist starred.
7.0
3-6
AD910L
Keywords: Books and reading -- Fiction; Libraries -- Fiction; Books and reading -- Fiction; Libraries -- Fiction; Books and reading -- Fiction; Libraries -- Fiction; Baghdad (Iraq) -- Fiction; Iraq -- Fiction